School climate’s effect on hospitality department students’ aesthetic experience, professional identity and innovative behavior - Lin, Weixin; Chang, Yuan-Cheng (Frontiers in Psychology, 2022)
This study investigated the effects of school climate and students’ aesthetic experience on their professional identity and innovative behavior. A survey was conducted with 385 students from hospitality-related departments of colleges and universities in Hainan, China, and the data were analyzed using a hierarchical linear model (HLM). Using the criteria constituting the students’ aesthetic experience scale proposed by Chang, it was found that teacher support can improve students’ professional identity; school climate and students’ understanding of beauty and full experience contribute to the development of students’ innovative behavior; students’ understanding of beauty and full experience have mediating effects between teacher support and professional cognition; students’ understanding of beauty and full experience have mediating effects between student support and innovative behavior; student support positively moderates the relationships between full experience with professional cognition and students’ appraisal of the hospitality industry; and teacher support positively moderates the relationship between students’ full experience and professional emotion. Therefore, teacher support under school climate and students’ understanding of beauty and full experience under aesthetic experience were the most important factors in enhancing hospitality department students’ professional identity and innovative behavior.